The online world of surrogacy - Berend, Zsuzsa (Fertility, reproduction, and sexuality, 2016)
Zsuzsa Berend presents a methodologically innovative ethnography of SurroMomsOnline.com, the largest surrogacy support website in the United States. Surrogates' views emerge from the stories, debates, and discussions that unfold online. The Online World of Surrogacy documents these collective meaning-making practices and explores their practical, emotional, and moral implications. In doing so, the book works through themes of interest across the social sciences, including definitions of parenthood, the symbolic role of money, reproductive loss, altruism, and the moral valuation of relationships.